Bioprospecção de fungos endofíticos da alga vermelha Pyropia spiralis - Costa, Luis Paulo de Sousa [UNESP] (2016)
This work dealt with the study of fungal strains Sarocladium strictum (Ps-02) e Coniothyrium sp. (Ps-03) associated to the red macroalga Pyropia spiralis, collected at SP State shore. Their extracts were obtained in different culture media: rice, malt and Czapek, which induced diversified metabolic production, as shown by HPLC-DAD and NMR analyses and evidenced that the metabolic profile depends on culture media for these strains. Extracts and fractions from Sarocladium strictum and Coniothyrium sp. were evaluated in antifungal, anticholinesterasic and cytotoxic assays and presented one or more potential bioactivities. Fraction Ps-03 A-ACN from Coniothyrium sp. showed antifungal and cytotoxic activities, and was selected for reversed phase column chromatography under positive pressure and gradient elution with H2O:MeOH. Fractions purification by HPLC-DAD or normal phase column chromatography led to the isolation of one diketopiperazine, polyketides and steroids, which had their structural elucidation by UV, 1D and 2D NMR, and MS analyses. The polyketides isolated in this study include three aromatic macrolides (1 – 3): (3R,5R)-sonnerlactone and two sonnerlactone analogues: one novel compound and one novel as a natural product; the aromatic butenolide gymnoascolide A (4), and the antiviral tetralone 10-norparvulenone (7). Two steroids: ergosterol-5,8-endoperóxido-∆6,22 (5) and 22E-ergosta-7,22-dieno-3β,5,6-triol (6) were also isolated. They are structurally related, probably due to rearrangement, which includes opening of the endoperoxide ring and double bond shift. Compound 8 is a diketopiperazine, that results from one unit phenylalanine and one of threonine. Such results confirm the strong chemodiversity of marine-derived endophytic fungi and their relevant bioactivity potential, which represents an open and attractive path towards deeper bioprospection studies on such ecological niche.